PERBEDAAN GANGGUAN MOBILITAS DITINJAU BERDASARKAN KARAKTERISTIK PASIEN OSTEOARTRITIS LUTUT DI POLI REHABILITASI MEDIK RSUD ULIN BANJARMASIN - Sari, Nanda Haliza; Siddik, Muhammad; Sanyoto, Didik Dwi; Arsyiana, Fathia; Putera, Husna Dharma (Universitas Lambung Mangkurat, 2024)
Abstrak : Osteoarthritis (OA) is a commonly encountered joint disease resulting from a degenerative and inflammatory process in the area of the joint cartilage. In individuals with this condition, the joint cartilage has worn away, causing an uneven and rough joint surface. The knee joint is particularly susceptible to OA. Knee OA causes primary symptoms of pain and stiffness in the joint, resulting in mobility issues. This study aims to ascertain the differences in mobility impairment based on the characteristics of knee osteoarthritis patients at the Medical Rehabilitation Outpatient Clinic of Ulin Regional General Hospital, Banjarmasin. This research constitutes an analytical observational study with a cross-sectional design, involving a sample comprising all knee OA patients with mobility impairments referred to and recorded at the medical rehabilitation outpatient clinic of Ulin Regional General Hospital, Banjarmasin, during the period of November 2023. The findings of this study revealed that one of the six patient characteristics, namely, the classification of knee OA severity based on Kellgren-Lawrence, is associated with mobility impairment. Keywords : knee osteoarthritis, mobility impairment, patient charactheristics. Abstrak : Osteoartritis (OA) merupakan jenis penyakit sendi yang sering dijumpai dan terjadi akibat proses degeneratif sekaligus peradangan pada daerah tulang rawan sendi. Pada penderita penyakit ini, tulang rawan sendi telah mengalami penipisan atau aus sehingga menyebabkan permukaan rawan sendi menjadi tidak rata dan bergelombang. Sendi pada lutut merupakan sendi yang rentan terkena OA. Penyakit OA lutut menyebabkan gejala utama nyeri dan kaku pada sendi lutut sehingga mengakibatkan masalah gangguan mobilitas. Penelitian ini bertujuan untuk mengetahui perbedaan gangguan mobilitas ditinjau berdasarkan karakteristik pasien osteoartritis lutut di Poli Rehabilitasi Medik RSUD Ulin Banjarmasin. Penelitian ini merupakan penelitian observasional analitik dengan desain cross sectional, sampel yang diambil merupakan seluruh pasien OA lutut dengan gangguan mobilitas yang dirujuk dan terdata di poli rehabilitasi medik RSUD Ulin Banjarmasin periode November 2023. Hasil dari penelitian ini didapatkan 1 dari 6 karakteristik pasien yaitu klasifikasi derajat OA lutut berdasarkan kellgren-lawrence memiliki hubungan dengan gangguan mobilitas. Kata-kata kunci: osteoartritis lutut, gangguan mobilitas, karakteristik pasien.